Cover Feature: Structural Studies of Norditerpenoid Alkaloids: Conformation Analysis in Crystal and in Solution States (Eur. J. Org. Chem. 15/2021). Issue 15 (1st April 2021) - Zeng, Ziyu; Kociok‐Köhn, Gabriele; Woodman, Timothy J.; Rowan, Michael G.; Blagbrough, Ian S.
Abstract : The Cover Feature shows the simplified X‐ray structures of four biologically important norditerpenoid alkaloids. On the left are the well‐known poison, aconitine and the clinically used lappaconitine. These two are natural products isolated from Aconite plants (in the background). The right‐hand flowers are Delphiniums, from which methyllycaconitine and lycoctonine are obtained. Methyllycaconitine, one of the most potent and selective nAChR antagonists, does not show any of the biological activity of aconitine. Lycoctonine has lost the biological activity by losing the key aromatic side‐chain. More information can be found in the Full Paper by I. S. Blagbrough et al.